The Multilevel Analysis of the Social Network in the Older Adults on the Urban-Heart 2 - Seyed Hamid Nabavi; Mohsen Asadi-Lari; Mir-Taher Mousavi; Vahid Rashedi; Reza Fadayevatan (University of Social Welfare & Rehabilitation Sciences, 2022)
Objectives Social network in older adults refers to interpersonal relationships and the perception of these relationships. Given the importance of the social network, the current study was conducted to answer three pivotal questions. First, do personal and regional factors affect the social network of the elderly? Second, how much share do the individual and regional factors have in the social network of the elderly? And third, which of these factors affect the social network of the elderly at each level of the personal and regional relationships. Methods & Materials The study was conducted based on the second round of the Tehran city health equity and response tool (Urban-Heart 2). Thus, 5760 individuals (age <60 year) were selected from 22 urban regions in Tehran City. These data were then analyzed using the multilevel regression model. Results The personal and regional levels explained about 89% and 11% of the social network of the elderlies, respectively. The individual factors explained 21% of the variance in the social network. Out of these parameters, age between 60 and 74, illiteracy, self-reported health, and mental health affected the social network significantly. At the regional level, the feeling of security, the control of corruption, the waiting time for bus arrival, and the sense of responsibility were the most influential factors explaining 19% of the variance in the social network. Conclusion Not only is the social network of the elderlies affected by personal factors such as age, education level, and self-reported health and mental health, but it is also affected by regional factors (feeling of security, the control of corruption, the sense of responsibility, and waiting time for bus arrival). Although these regional factors are out of personal control, they can be improved for the elderly in society.